European urban public transport: towards a single European employment model?. (1st April 2010) - ,; ,
Abstract : Publicly owned public transport contributed to the distinctive character of 20th century European cities. Today, however, the sector is being opened up to various forms of competition. Using a comparative study of urban public transport in six European countries, this paper traces the emergence of a new European mode of regulation for the sector. This new framework has not, however, always led to a deterioration in wages or working conditions, since national employment systems remain important. Change has often been justified as leading to improved service quality: traditional public sector employment, above all job security, was seen as contributing to bad service for passengers. Our study, undertaken as part of the EU-funded Dynamo project, however finds no such simple link — either negative or positive — between the quality of service and the nature of employment.